2014
DOI: 10.1016/s2213-2600(14)70008-6
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to diagnose chronic obstructive pulmonary disease in routine care in the UK: a retrospective study of a clinical cohort

Abstract: UK Department of Health, Research in Real Life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 40 publications
7
140
0
1
Order By: Relevance
“…Estimates by the Department of Health in the UK indicate that approximately 2.2 million people are still undiagnosed [1].This has been corroborated by a recent study, which showed that the chances of early diagnosis of COPD by doctors in the UK have been missed in 85% of cases in the five years before the actual diagnosis [41]. In the USA, 12.7 million people have COPD.…”
Section: Discussionmentioning
confidence: 91%
“…Estimates by the Department of Health in the UK indicate that approximately 2.2 million people are still undiagnosed [1].This has been corroborated by a recent study, which showed that the chances of early diagnosis of COPD by doctors in the UK have been missed in 85% of cases in the five years before the actual diagnosis [41]. In the USA, 12.7 million people have COPD.…”
Section: Discussionmentioning
confidence: 91%
“…Quantitative studies Sp1,Sp2,Sp16,Sp19,Sp52,Sp54,Sp55,Sp62,Sp63,Sp87 Sp8,Sp9,Sp15,Sp43,Sp75,Sp87,Sp89,Sp90,Sp92,Sp97 Sp6,Sp14,Sp16,Sp18,Sp27,Sp36,Sp47,Sp49,Sp55,Sp60,Sp61,Sp64,Sp88,Sp100 Sp2,Sp57,Sp59,Sp68,Sp108 Qualitative studies…”
Section: Sp21mentioning
confidence: 99%
“…Jones et al found that opportunities to diagnose COPD at early stages are being missed several years ahead of diagnosis. They emphasize the importance of prioritizing educating of nurses and doctors to identify people at risk (including comorbidity) and patients with lower respiratory symptoms, so spirometry can be performed early on [26]. …”
Section: Discussionmentioning
confidence: 99%